The impact of hysterectomy on oncological outcomes in postmenopausal patients with borderline ovarian tumors: A multicenter retrospective study - Raimondo, Diego; Raffone, Antonio; Scambia, Giovanni; Maletta, Manuela; Lenzi, Jacopo; Restaino, Stefano; Mascilini, Floriana; Trozzi, Rita; Mauro, Jessica; Travaglino, Antonio; Driul, Lorenza; Casadio, Paolo; et al. (Frontiers in Oncology, 2022)
Data about the oncological outcomes in women with borderline ovarian tumor (BOT) undergoing uterine-sparing surgery without ovarian preservation are poor. We aimed to assess the oncological outcomes in women with BOT undergoing uterine-sparing surgery without ovarian preservation. A multi-center observational retrospective cohort study was performed including all consecutive postmenopausal patients who underwent surgical treatment for BOT at three tertiary level referral centers for gynecologic oncology from January 2005 to December 2016. Patients were divided into two groups for comparisons: patients undergoing hysterectomy (hysterectomy group) and patients undergoing uterine-sparing surgery (no hysterectomy group). Study outcomes were disease-free survival (DFS), overall survival (OS), disease-specific survival (DSS) and surgical complications rate. Ninety-eight patients were included: 44 in the hysterectomy group and 54 in the no hysterectomy group. The 5- and 10-year DFS rates were 97.7% (95% CI: 84.9–99.7) and 92.3% (95% CI: 69.7–98.2), in the hysterectomy group, and 86.8% (95% CI: 74.3–93.5) and 86.8% (95% CI: 74.3–93.5), in the no hysterectomy group, respectively, without significant differences (p=0.16). Hazard ratio for DFS was 0.26 (95% CI: 0.06–1.68) for the hysterectomy group. The 5- and 10-year OS rates were 100.0% (95% CI: -) and 100.0% (95% CI: -), in the hysterectomy group, and 98.2% (95% CI: 87.6–99.7) and 94.4% (95% CI: 77.7–98.7), in the no hysterectomy group, respectively, without significant differences (p=0.23). No significant difference in complication rate was reported among the groups (p=0.48). As hysterectomy appears to not impact survival outcomes of women with BOT, it might be avoided in the surgical staging.